Brain-derived neurotrophic factor Val66Met and neuropsychological functioning after early childhood traumatic brain injury. (25th March 2023) - Treble-Barna, Amery; Wade, Shari L.; Pilipenko, Valentina; Martin, Lisa J.; Yeates, Keith Owen; Taylor, H. Gerry; Kurowski, Brad G.
Abstract: Objective: The present study examined the differential effect of the brain-derived neurotrophic factor (BDNF) Val66Met polymorphism on neuropsychological functioning in children with traumatic brain injury (TBI) relative to orthopedic injury (OI). Methods: Participants were drawn from a prospective, longitudinal study of children who sustained a TBI ( n = 69) or OI ( n = 72) between 3 and 7 years of age. Children completed a battery of neuropsychological measures targeting attention, memory, and executive functions at four timepoints spanning the immediate post-acute period to 18 months post-injury. Children also completed a comparable age-appropriate battery of measures approximately 7 years post-injury. Parents rated children's dysexecutive behaviors at all timepoints. Results: Longitudinal mixed models revealed a significant allele status × injury group interaction with a medium effect size for verbal fluency. Cross-sectional models at 7 years post-injury revealed non-significant but medium effect sizes for the allele status x injury group interaction for fluid reasoning and immediate and delayed verbal memory. Post hoc stratified analyses revealed a consistent pattern of poorer neuropsychological functioning in Met carriers relative to Val/Val homozygotes in the TBI group, with small effect sizes; the opposite trend or no appreciable effect was observed in the OI group. Conclusions: The results suggest a differential effect of the BDNF Val66Met polymorphism on verbal fluency, and possibly fluid reasoning and immediate and delayed verbal memory, in children with early TBI relative to OI. The Met allele—associated with reduced activity-dependent secretion of BDNF—may confer risk for poorer neuropsychological functioning in children with TBI.